Geographical Disadvantage: A Heckscher-Ohlin-von Thunen Model of International Specialization. - Venables, A; Limao, N (2002)
We analyse the trade and production patterns of countries located at varying distances from an economic centre. Exports and imports of final and intermediate goods bear transport costs which increase with distance. We show how production and trade depend on factor endowments and factor intensities, and also on countries' locations and the transport intensities of different goods. Countries divide into zones with different trade patterns, some export oriented and others import substituting. We study the implications of distance for factor prices and real incomes, the effects of changes in transport costs, and the locational choice of new activities.